2018
DOI: 10.16993/sjdr.59
|View full text |Cite
|
Sign up to set email alerts
|

‘Behind This Wall’ – Experiences of Seclusion on Locked Wards for Women

Abstract: Aim: To more fully understand the experiences of seclusion in a learning disability service for women. Background: This paper reports on one of the analytical themes, seclusion, from an ethnographic study exploring the lives of learning disabled women on locked wards. Method: Participant observation was used on three locked wards for women in a learning disability secure (forensic) unit in the United Kingdom. Themes from the analysis of field-notes were used to construct an interview schedule. Sixteen detained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Fish (2018) found that incidents of aggression or self‐harm can work to keep a person longer in a unit. Importantly, a staff member here describes how good relationships can work to reduce incidents of aggression, therefore bringing about stability:
Iona: My attitude towards her was very upbeat and very OK.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish (2018) found that incidents of aggression or self‐harm can work to keep a person longer in a unit. Importantly, a staff member here describes how good relationships can work to reduce incidents of aggression, therefore bringing about stability:
Iona: My attitude towards her was very upbeat and very OK.
…”
Section: Resultsmentioning
confidence: 99%
“…Drawing on our previous research, and that by Head et al, it is clear that relationships are an important factor in the well‐being of residents including their ability to move through the services and be discharged successfully into the community (Fish, 2017; Fish & Duperouzel, 2008; Fish & Morgan, 2019; Head et al, 2018). However, there are multiple challenges to the building of relationships, related to the requirement for maintaining boundaries and professionalism on behalf of staff, and self‐sufficiency on behalf of residents (Fish, 2016, 2018; Parkes & Freshwater, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies explored staff,148–157 patient147 158–165 and mixed groups’166–173 views and experiences of seclusion and restraint. Nine studies focused on the processes surrounding seclusion and restraint 136 137 174–180.…”
Section: Resultsmentioning
confidence: 99%
“…Østvik et al (2018) pick this theme up in the new issue, exploring how friendships between disabled children using augmentative and alternative communication and non-disabled children can be facilitated or inhibited in mainstream primary school settings. The problems of institutional segregation to lack of opportunities for privacy (Fish, 2018), or lack of social participation and exclusion from the surrounding community (Søndenaa et al, 2018) is also present in the new issue.…”
Section: Where We Are Nowmentioning
confidence: 99%